Organization Ethics as the Tool for Management Optimization - Vasiljevienė, Nijolė (Ekonomika, 2004)
The author of the paper maintains that new blocks of knowledge about scientificallybased human resource augmentation and social order (re)construction has formed recently. The possibilities of social order reconstruction are realized through implementation of ethics infrastructure tools in organizations, enterprises and institutions. Namely organization ethics as the interdisciplinary junction determined this. The aim of this paper is to emphasize thoroughly the fact that such a means of human resource augmentation, management optimization, improvement of social capital not only has not exhausted, but even has not adequately grasped yet. The matters stands in this way since human resources are often interpreted only quantitatively without taking into account the quality of interpersonal relations system, the (people) behaviour in a workplace, decisive impact of the positive/negative circumstances in organizations and institutions upon human abilities/inabilities, that is directly upon the resources of human being, his capability to perform his functions properly, in socially responsible manner. In modem organizations during the processes of human resource formation or (re)construction the value management is implemented, when the values of responsibility, fairness, honesty, integrity, transparency, and trust are emphasized. These values stipulate (determine) the environment that promote realization of positive properties of Human being and his appropriate behavioural habits. Without formation of solid network of such [relations] the human resources cannot be increased in the direction of prospective capabilities. Simultaneously the paper tackles the vistas of successful solution of the problems involved, stresses the necessity to acquire the adequate knowledge about possibilities to optimize management by the means of business ethics that inculcates values in organization life through managerial methods. It is stressed that acquisition of these knowledges should be purposively accelerated in Lithuania for the sake of economic effectiveness and competitiveness of the nation. In contemporary epoch people carry out their labour activity in organizations: undertakings, institutions, schools, hospitals etc. that is why business ethics like any other kind of professional (applied) ethics becomes organizational ethics and is stipulated for the peculiarities of an organization. That is why the responsibility for the proper behaviour - good work - is now being transferred from the person to the structure he works in. that is the responsibility is “mounted on” the environment that motivate/demotivate him to behave properly. The necessity to grasp and apply the idea of organizational (corporate) responsibility in enterprises determines purposeful institutionalization of business ethics. For this purpose first of all it should be indicated what is to be done in enterprises in order to make it easier for employees to be decent (responsible, reliable, good-working professional)? What are the definite conditions and circumstances arc necessary to motivate a person to observe rules, norms and laws. The proper behaviour of a person is often constrained namely by the wrong management in the organization: it is directly determined by institutional order/disorder. The paper scrutinizes how the process of business ethics institutionalization enables to improve soundly organizational performance, to change the actual state of affairs, not only to create the image of an organization or enterprise, its abstract culture. Building of moral competence constitutes the investment into the real resolution of practical issues instead of creation of a sham image. It is the way to reach the conformity of “is” and “ought”, practice and declared principles, to bring the words (organizational “missions” or “visions”) into line with real deeds through managerial techniques. It is also the way to reach the integrity of the organizational culture and hence to win the trust of clients, consumers and stakeholders. It yields good reputation, competitive ability, increases the demand for goods and services, which make more profit. For this purpose instrumental, scientifically based creation of real organizational values - trust, responsibility, compliance, transparency, and integrity, - are implemented in organisations’ activity. The scientists from different countries have studied the phenomena of organizational ethics and appropriate cause-effect relations and came to the conclusion that the organizational causes of unethical (indecent) behaviour are rather typical, and the dysfunctions and pathologies in organizations are oft-recurring. It means they are determined by regularities, that is why they should be removed by the managerial methods. Hence it stipulates formation of the Deed in adjustable, managed ethics. This kind of ethics in fact is already integrated into the very managerial actions, to put more precisely management is ethics-filled. Namely hypercompetitive market demands such a management that is why the new scientificallybased, supported by ethics infrastructure managerial technologies are rapidly developing. Proceeding from the fact that he most part of people activity conditions are stipulated by their definite behaviour, than one can cognize, find out their causes and then master them rationally: to (re)model, to form and to change. The new managerial systems developed from the codes of conduct and social standards in the West have already formed not only theoretically but also in practice. Hence it is very topical for today Lithuania to overcome general backwardness in this aspect of managerial theory and practice to make possible real integration of scientific discoveries in junction of modem managerial science, applied ethics and business practice.